1998
DOI: 10.4269/ajtmh.1998.59.722
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of visceral leishmaniasis in central Israel.

Abstract: Abstract. In 1994-1995, a child and five dogs from villages located between Jerusalem and Tel-Aviv, Israel were diagnosed with visceral leishmaniasis (VL). Based on these findings, the distribution of VL in domestic and wild canids in central Israel was examined. In the two villages where canine index cases were identified, a substantial proportion (11.5%, 14 of 122) of the dogs examined were seropositive. However, the rate of infection in five neighboring villages was only 1% (1 of 99). Parasites were culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 8 publications
0
47
1
2
Order By: Relevance
“…Human and canine VL reemerged in central Israel after an absence of more than 30 years (5,22). Even though VL cases were not reported from this region during the intervening period of 1960 to 1993, sporadic cases of infantile HVL continued to occur in northern Israel (2,15,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human and canine VL reemerged in central Israel after an absence of more than 30 years (5,22). Even though VL cases were not reported from this region during the intervening period of 1960 to 1993, sporadic cases of infantile HVL continued to occur in northern Israel (2,15,22).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that active transmission still occurs in Galilee, even though the number of clinical cases is small (2). In 1994, after an absence of Ͼ30 years, index cases of HVL and CVL were diagnosed in central Israel (5). Since then, an additional 27 foci and numerous cases of CVL have been identified in this region by passive and active surveillance.…”
Section: Human Visceral Leishmaniasis (Vl) (Hvl) Caused By Leishmaniamentioning
confidence: 99%
“…The cut-off value was set at 0.6OD [2]. IgG subclasses were measured in sera obtained from the L. infantum -EI dogs before infection, at 2, 4, 6 and 8 weeks, 3, 5 and 7 months post-infection, and at 7 months after treatment was stopped (Suppl.…”
Section: Total Igg and Igg Subclass Elisamentioning
confidence: 99%
“…Cases of VL from the vicinity of Bethlehem south of Jerusalem 5 and from the village of Bal'a in the north western Tulkarm district 6 have been reported during the last two decades. The apparent recent increase in the occurrence of human VL in West Bank hospitals and the emergence of this disease in neighboring Central Israel 7 warranted a current epidemiological appraisal of the existence and recent spread of this potentially fatal illness among the Palestinian population in the West Bank. Based on preliminary data from the Palestinian Ministry of Health, which indicated that VL is highly prevalent and is spreading in the Jenin district of the northern West Bank, a study on the disease in this district was initiated.…”
Section: Introductionmentioning
confidence: 99%